Preoperative anxiety among patients undergoing cardiac surgery: a cross-sectional study from a tertiary care hospital in rural Tamil Nadu - Hema Rajendran, Naveen; Chandrasekaran, Sundhareshwaran; Thayyil, Prasandan; Jayakumar (International Journal Of Community Medicine And Public Health, 2025)
Background: Preoperative anxiety is a common yet under-recognized concern among patients undergoing cardiac surgery. It can adversely affect hemodynamic stability, postoperative recovery, and patient satisfaction. Despite its clinical relevance, limited data exist from semi-urban tertiary care centers in South India. This study aimed to assess the prevalence and predictors of preoperative anxiety among patients undergoing elective cardiac surgery using the Amsterdam preoperative anxiety and information scale (APAIS) and the visual analog scale for anxiety (VAS-A). Methods: A hospital-based cross-sectional study was conducted among 250 adult patients scheduled for elective cardiac surgery at a tertiary care hospital in Tamil Nadu. Data on sociodemographic and clinical variables were collected using a semi-structured questionnaire. Anxiety was assessed using APAIS and VAS-A. APAIS≥11 was used to define clinically significant anxiety. Results: The mean age of participants was 56.2±11.3 years; 60.8% were male. The prevalence of clinically significant anxiety (APAIS≥11) was 56.4%. The mean APAIS and VAS-A scores were 11.9±3.8 and 5.8±2.3, respectively. Female gender (AOR: 1.89; 95% CI: 1.15-3.12), absence of prior surgical experience (AOR: 2.21; 95% CI: 1.29-3.81), hypertension (AOR: 1.78; 95% CI: 1.05-3.03), and education below graduation (AOR: 1.65; 95% CI: 1.01-2.72) were significant predictors of high anxiety. A significant positive correlation was observed between APAIS and VAS-A scores (r=0.61, p<0.001). Conclusions: Preoperative anxiety is highly prevalent among cardiac surgery patients and is influenced by gender, age group, family type and prior surgical experience. Routine screening using simple validated tools like APAIS and VAS-A can enable timely psychological support and preoperative counselling, potentially improving surgical outcomes.